Plan de negocios para la creación de una empresa comercializadora de jalea de maracuyá con ají - Paredes Villegas, John Steven (2020)
The purpose of this business plan is to develop an innovative food product based on the combination of exotic fruits such as passion fruit and chili, together in a jelly, obtaining a sweet flavor due to the essence of passion fruit, with a spicy touch of chili pepper in search of capturing the attention of the final consumer. In chapter one, the problem and the justification of the project were raised, in which, the business opportunities that can be exploited are detailed; as well as the delimitation of the project where the planning for the development of the business plan is carried out. In the second chapter, all the theoretical bases on which to support the research were raised and which will be the foundations in the planning of the business plan………